Technology of the information and communication in public and private schools in Arequipa - Walter Lizandro Arias Gallegos (Interacciones)
In this study we made a frequency and percentage analysis of TIC in Arequipa City (Peru) in order to identify the most frequent ICTs in school context and settle a comparison between private and public schools. It was designed a survey and applied in 83 schools (51 private y 32 public) that were selected by probabilistic methods. The results suggest that the access to ICTs is low in both types of schools but minor in public school. The most frequent ICTs were the computer, television, DVD player, radio and internet.